Do savings increase in response to salient information about retirement and expected pensions? - Mathias Dolls; Philipp Doerrenberg; Andreas Peichl; Holger Stichnoth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
How can retirement savings be increased? We explore a unique policy change in the context of the German pension system to study this question. As of 2004, the German pension authority started to send out annual letters providing detailed and comprehensible information about the pension system and individual expected pension payments. This reform did not change the level of pensions, but only manipulated the knowledge about and salience of expected pension payments. Using German tax return data, we exploit two discontinuities in the age cutoffs of receiving such a letter to study their effects on private retirement savings. Our results show that the letters increase private retirement savings. The effects are fairly sizable and persistent over several years. We further show that the letter increases labor earnings, and that the increase in savings partly crowds out charitable donations. Moreover, we present evidence suggesting that both information and salience drive the savings effect. Our paper adds to a recent literature showing that policies that go beyond the traditional neoclassical reasoning can be powerful to increase savings rates.
urn:nbn:de:bsz:180-madoc-414224
Keywords: H55; H24; J26; D14; 330; pensions; savings; salience; information